Effect of the thermal storage medium on non-dimensional numbers of a grain dryer (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study deals with the evaluation of non-dimensional numbers such as Grashof numbers, Rayleigh numbers, and Nusselt numbers for the outer surface of the rectangular chamber of biomass operated natural convection crop dryer. This study is aimed to develop a grain dryer for agricultural products drying in the village areas of the developing countries, especially where electricity is not available. This study has been performed for the two cases; (i) without thermal storage medium in the rectangular chamber, and (ii) with thermal storage medium in the chamber. The purpose of this study is to analyze whether the thermal storage reduces the energy losses from the rectangular chamber. The non-dimensional numbers analysis has been performed for both the cases of studies. In the present study, variations in all the non-dimensional numbers with time were plotted. Relatively lower values of the non-dimensional numbers for the chamber outer surface were obtained for the case-II. Hence, the thermal storage medium reduces the energy losses from the chamber